2023
DOI: 10.54203/scil.2023.wvj21
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Antimicrobial Susceptibility of Salmonella spp. Isolated From Commercial Eggs in Tiaret Province, Algeria

Abstract: Salmonellosis is a significant public health problem worldwide. The current study aimed to investigate the presence of Salmonella spp. in commercial eggs of Tiaret province, Algeria, and evaluate the susceptibility of isolated strains to different antimicrobial agents. A total of 180 commercial eggs collected from various retail outlets (groceries, butchers, wholesalers, street vendors) were analyzed by conventional methods, and 13 Salmonella spp. isolates were tested on a panel of 7 antimicrobial agents using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
1
1
2
Order By: Relevance
“…However, all the strains in both serotypes were resistant to colistin. These results contrast with similar studies that reported either sensitivity or very low resistance to colistin (Bahramianfard et al., 2021; Merati & Boudra, 2023). The high resistance to colistin among the Salmonella strains isolated in this study and the risk of horizontal gene transfer indicates that the indiscriminate use of colistin in poultry may threaten public health.…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations
“…However, all the strains in both serotypes were resistant to colistin. These results contrast with similar studies that reported either sensitivity or very low resistance to colistin (Bahramianfard et al., 2021; Merati & Boudra, 2023). The high resistance to colistin among the Salmonella strains isolated in this study and the risk of horizontal gene transfer indicates that the indiscriminate use of colistin in poultry may threaten public health.…”
Section: Discussioncontrasting
confidence: 92%
“…Based on studies carried out in Iran and other countries on contaminated eggs, the most common isolated serotypes of hen eggs include S. enteritidis and S. typhimurium (Hosseininezhad et al., 2020; Merati & Boudra, 2023; Sabeer & Abeer, 2019), which is consistent with the results of our study. The prevalence of S. enteritidis is due to its vertical transmission and colonization in the hen reproductive system, which can contaminate the contents and the shell.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations